DEVIASI GRAMATIKA DALAM TULISAN MAHAHASISWA JURUSAN BAHASA INGGRIS DI STKIP MUHAMMADIYAH BULUKUMBA - Syahriani, Irma; Kamsina, Kamsina; Pammu, Abidin (JURNAL ILMU BUDAYA, 2018)
The reason for conducting this research was based on consideration that university students majoring in English should be at the level where their English is good. Unfortunately, students still made grammatical deviations in both spoken and written form. In this study, 30 students of STKIP Muhammadiyah Bulukumba University enrolled which were taken by random sampling method. This research is aimed to provide useful information particularly as reference for English teachers, lecturers and curriculum developers about grammatical deviations that affects the quality of students’ writing composition to minimize it. This research applied the qualitative research to analyze the data. The conclusion of the result shows that the students still have problems in making English sentences. They still make grammatical deviations in their composition. They were also not being able to construct words into sentences and arranged sentences into neat arrangements and coherent paragraphs.Further, syntactical area is the most frequent area where the students committed grammatical deviation. It is proven by the findings thatsyntax is considered to be more difficult than morphology. It appears that the students’ errors distribute to all students’ writings. They still make grammatical deviation, but the students do not always make grammatical deviations in the samesubcomponent.In terms of difficulties, the students admitted in interview that there are 3 main causeswhy the students tend to commit grammatical deviation in writing. Those are lack of practice of the target language, lack of source or books that they need, and the last is lack of grammar understanding.